2020
DOI: 10.1098/rstb.2019.0453
|View full text |Cite
|
Sign up to set email alerts
|

Ecological limits to evolutionary rescue

Abstract: Environments change, for both natural and anthropogenic reasons, which can threaten species persistence. Evolutionary adaptation is a potentially powerful mechanism to allow species to persist in these changing environments. To determine the conditions under which adaptation will prevent extinction (evolutionary rescue), classic quantitative genetics models have assumed a constantly changing environment. They predict that species traits will track a moving environmental optimum with a lag that approaches a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 57 publications
(71 reference statements)
2
42
0
Order By: Relevance
“…More generally, Bernhardt et al [59] conceptualize the ability of organisms to cope with such variability, and complement the feedback strategies, where organisms respond to changes in conditions by feed-forward mechanisms, where they adjust to anticipated future changes in conditions via sensing the environment. Klausmeier et al [60] then ask how evolutionary adaptation to changing conditions can occur and whether it can be fast enough to prevent extinction. They review different approaches to modelling evolutionary rescue, and finally propose a new approach that explicitly includes bounded environmental changes and limits to adaptation.…”
Section: Contributions To This Issuementioning
confidence: 99%
“…More generally, Bernhardt et al [59] conceptualize the ability of organisms to cope with such variability, and complement the feedback strategies, where organisms respond to changes in conditions by feed-forward mechanisms, where they adjust to anticipated future changes in conditions via sensing the environment. Klausmeier et al [60] then ask how evolutionary adaptation to changing conditions can occur and whether it can be fast enough to prevent extinction. They review different approaches to modelling evolutionary rescue, and finally propose a new approach that explicitly includes bounded environmental changes and limits to adaptation.…”
Section: Contributions To This Issuementioning
confidence: 99%
“…In general, trait‐based eco‐evolutionary models typically assume that maximum growth is a unimodal function of trait, which is satisfied by both Gaussian and quadratic functions. We note that while the exact shapes of fitness functions remain largely unknown (Klausmeier et al 2020 , Osmond and Klausmeier 2017 ), both types explored here can locally approximate any smooth, general fitness function (Shaw and Geyer 2010 ).…”
Section: Model and Methodsmentioning
confidence: 98%
“…We do not expect our model to be predictive for organisms reproducing with low recombination rates if multiple rescue mutations are required for restoring positive growth rates, as we neglected competition between beneficial mutations [Gerrish and Lenski, 1998] or competition in other ecological contexts (e.g. Osmond and de Mazancourt [2013], Klausmeier et al [2020]). It has also been shown that the shape of the distribution of fitness effects as well as the recombination rate between loci harbouring rescue mutations can play an important role [Uecker and Hermisson, 2016, Anciaux et al, 2018.…”
Section: Discussionmentioning
confidence: 99%